Preparation method of simple crystal structure high-entropy alloy composite material
Patent Information
- Application Number
- CN202410306442.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-18
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-03-18
AI Technical Summary
[0003]因为现有06Cr19Ni10奥氏体不锈钢硬度低,所以现在急需提供一种新的材料以代替现有的06Cr19Ni10奥氏体不锈钢
[0013](1)可通过控制高熵合金中铬元素的含量变化以及通过镀镍碳纳米管的加入提高其硬度以及耐蚀性进而替代06Cr19Ni10奥氏体不锈钢材料,成为一种更优异的新型工程材料。
Smart Images

Figure CN118308641B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing a high-entropy alloy composite material with a simple crystal structure, belonging to the field of composite material technology. Background Technology
[0002] With the development of modern industry, the requirements for the performance and quality of traditional steel are becoming increasingly stringent. Currently, the most commonly used stainless steel is the national standard 06Cr19Ni10 austenitic stainless steel, also known as 304 stainless steel. While stainless steel meets people's needs in various fields, it has also exposed two problems. On the one hand, existing stainless steel materials have relatively low hardness, making them prone to scratches on the surface, leading to surface treatment failure, exposing the internal structure of the material, and subsequently causing corrosion and structural damage. On the other hand, existing stainless steel materials have good corrosion resistance in alkaline environments and most acidic environments, but in neutral environments with chloride ions, corrosion is rapid, even exceeding that of ordinary low-carbon steel. This is because the corrosion resistance of stainless steel mainly stems from the formation of a dense, chromium-rich oxide film on the surface of the stainless steel under the action of oxygen in the air or under acidic or alkaline conditions, preventing internal corrosion.
[0003] Because existing 06Cr19Ni10 austenitic stainless steel has low hardness, there is an urgent need to provide a new material to replace it. High-entropy alloys, unlike alloys generally understood, are unusual because they are special alloys composed of multiple elements in equimolar or near-equimolar ratios. Thermodynamically, they exhibit a high-entropy effect; kinetically, a slow diffusion effect; structurally, a lattice distortion effect; and in terms of performance, a "cocktail" effect. Research shows that high-entropy alloys possess corrosion resistance far exceeding that of 06Cr19Ni10 austenitic stainless steel, as well as better mechanical properties. By adding nickel-plated carbon nanotubes as a reinforcing phase, the hardness and compressive strength of the material can be further enhanced, perfectly replacing the original stainless steel material. Summary of the Invention
[0004] To address the low hardness of existing 06Cr19Ni10 austenitic stainless steel, this invention provides a method for preparing a simple high-entropy alloy composite material with a high-entropy crystal structure. By controlling the chromium content in the high-entropy alloy and adding nickel-plated carbon nanotubes as a reinforcing phase to the high-entropy alloy matrix, its compressive strength and hardness can be improved while meeting corrosion resistance requirements, thus replacing 06Cr19Ni10 austenitic stainless steel and becoming a superior new engineering material.
[0005] The high-entropy alloy is prepared using the following specific method:
[0006] (1) Metal powders of 7.3% to 9.3% Al, 15.2% to 19.3% Fe, 16% to 20.3% Co, 15.9% to 20.3% Ni, 17.3% to 21.9% Cu and the balance Cr are mixed and vacuum ball-milled according to mass percentage, wherein the total mass fraction of each metal powder is 100%, to obtain high entropy alloy powder.
[0007] (2) Add nickel-plated carbon nanotubes to the high-entropy alloy powder obtained in step (1). The amount of nickel-plated carbon nanotubes added is 0.2% to 1.2% of the high-entropy alloy powder. Continue ball milling to obtain a mixed powder of nickel-plated carbon nanotubes and high-entropy alloy.
[0008] (3) The nickel-plated carbon nanotube high-entropy alloy mixed powder obtained in step (2) is directly pressed into shape under a pressure of 14 MPa for 10 min.
[0009] (4) The pressed powder compact is first preheated to 200℃ at a heating rate of 10℃ / min and held for 0.5h, then heated to 1200℃ at a heating rate of 5℃ / min and held for 2h, and then cooled in the furnace. The vacuum degree throughout the sintering process is less than 1*10 -2 Pa yields an entropy alloy composite material.
[0010] Preferably, the ball-to-material ratio in the ball milling process is 10:1, and the ball milling speed is 300 rpm; in step (1), the ball milling time is 15 hours; in step (2), the ball milling time is 10 hours.
[0011] Preferably, the nickel-plated multi-walled carbon nanotubes have an inner diameter of 5–10 nm, an outer diameter of 10–20 nm, and a length of 10–30 μm.
[0012] Beneficial effects of the present invention
[0013] (1) By controlling the change of chromium content in high-entropy alloys and by adding nickel-plated carbon nanotubes, its hardness and corrosion resistance can be improved, thereby replacing 06Cr19Ni10 austenitic stainless steel and becoming a superior new engineering material.
[0014] (2) This invention uses nickel-plated carbon nanotubes as the reinforcing phase. By adjusting the chromium content, different high-entropy alloys are selected to meet the requirements of corrosion resistance. The amount of nickel-plated carbon nanotubes added is controlled, and the mechanical alloying, dry pressing and vacuum sintering processes are controlled in conjunction with high-energy ball milling under vacuum conditions. This minimizes the adverse effects of impurity elements on the matrix, allowing the high-entropy alloy to be fully alloyed. With the addition of carbon nanotubes, the material has excellent mechanical properties.
[0015] (3) Nickel-plated carbon nanotubes are the reinforcing phase. Adding carbon nanotubes can effectively compensate for the influence of pores that are easily generated when preparing materials by powder metallurgy. The nickel-plated carbon nanotubes are dispersed in the high-entropy alloy matrix. Because the nickel plating on the surface of the carbon nanotubes has good compatibility with the nickel content of the alloy matrix itself, it plays a role in connecting the matrix and optimizing the material properties, similar to the role of steel bars for cement in reinforced concrete. Attached Figure Description
[0016] Figure 1 This is a metallographic image of the high-entropy alloy composite material prepared in Example 1 of the present invention.
[0017] Figure 2 This is a metallographic image of the high-entropy alloy composite material prepared in Example 2 of the present invention.
[0018] Figure 3 This is a metallographic image of the high-entropy alloy composite material prepared in Example 3 of the present invention.
[0019] Figure 4 This is a metallographic image of the high-entropy alloy composite material prepared in Example 4 of the present invention.
[0020] Figure 5 This is a metallographic image of the high-entropy alloy composite material prepared in Comparative Example 3 of the present invention.
[0021] Figure 6 This is a hardness indentation test image of the high-entropy alloy composite material prepared in Example 2 of the present invention.
[0022] Figure 7 The particle size test diagrams are of the high-entropy alloy powders prepared in step (1) of Comparative Examples 1 to 5 of this invention.
[0023] Figure 8 The density test diagrams are of the high-entropy alloy materials prepared by comparative examples 1 to 5 of this invention. Detailed Implementation
[0024] The technical solution of the present invention will be further described below with reference to the accompanying drawings and specific embodiments. However, the following embodiments are merely simple examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention is determined by the claims.
[0025] Example 1
[0026] A method for preparing a high-entropy alloy composite material includes the following steps:
[0027] (1) Mix metal powders of 8.4% Al, 17.8% Fe, 18.7% Co, 18.7% Ni, 20% Cu and 16.4% Cr by mass percentage, add zirconia grinding balls at a ball-to-material mass ratio of 10:1, load the ball powder into a vacuum ball mill jar and place it in a planetary ball mill at a speed of 300 rpm for 15 h to obtain high entropy alloy powder.
[0028] (2) Add nickel-plated carbon nanotubes to the high-entropy alloy powder obtained in step (1) and perform vacuum ball milling to mix the powder. The amount of nickel-plated carbon nanotubes added is 0.2% of the high-entropy alloy powder. The inner diameter of the nickel-plated multi-walled carbon nanotubes is 5nm, the outer diameter is 10nm, and the length is 10μm. Continue vacuum ball milling for 10h to obtain nickel-plated carbon nanotube high-entropy alloy mixed powder.
[0029] (3) The nickel-plated carbon nanotube high-entropy alloy mixed powder obtained in step (2) is directly pressed and held at a pressure of 14 MPa for 10 min without binder. Then, in a vacuum sintering furnace, the program is set with a heating rate of 10℃ / min from 0 to 200℃, holding at 200℃ for 0.5 h, and a heating rate of 5℃ / min from 200 to 1200℃, holding at 1200℃ for 2 h. The program ends and the furnace is cooled to obtain the high-entropy alloy composite material.
[0030] Depend on Figure 1 Metallographic surface analysis revealed that the nickel-plated carbon nanotubes exhibited virtually no agglomeration within the material, and the 0.2% nickel-plated carbon nanotube additive phase showed good compatibility with the matrix phase. Furthermore, the material exhibited low porosity and high density at a sintering temperature of 1200℃.
[0031] Example 2
[0032] A method for preparing a high-entropy alloy composite material includes the following steps:
[0033] (1) Metal powders of 9.3% Al, 19.2% Fe, 20.4% Co, 20.4% Ni, 21.8% Cu and 8.9% Cr were mixed by mass percentage. Zirconia grinding balls were added at a ball-to-material mass ratio of 10:1. The balls were loaded into a vacuum ball mill jar and placed in a planetary ball mill and ball-milled at 300 rpm for 15 h to obtain high-entropy alloy powder.
[0034] (2) Add nickel-plated carbon nanotubes to the high-entropy alloy powder obtained in step (1) and perform vacuum ball milling to mix the powder. The amount of nickel-plated carbon nanotubes added is 0.5% of the high-entropy alloy powder. The inner diameter of the nickel-plated multi-walled carbon nanotubes is 10 nm, the outer diameter is 20 nm, and the length is 10 μm. Continue vacuum ball milling for 10 h to obtain nickel-plated carbon nanotube high-entropy alloy mixed powder.
[0035] (3) The nickel-plated carbon nanotube high-entropy alloy mixed powder obtained in step (2) is directly pressed and held at a pressure of 14 MPa for 10 min without binder. Then, in a vacuum sintering furnace, the program is set with a heating rate of 10℃ / min from 0 to 200℃, holding at 200℃ for 0.5 h, and a heating rate of 5℃ / min from 200 to 1200℃, holding at 1200℃ for 2 h. The program ends and the furnace is cooled to obtain the high-entropy alloy composite material.
[0036] Depend on Figure 2 , Figure 6 Analysis shows that the nickel-plated carbon nanotube additive phase with an addition of 0.5% exhibits good compatibility with the matrix phase, with few voids around the additive phase. The microcrystalline structure displays a regular arrangement of lamellar or dendritic structures, which is conducive to forming a stable micromechanical structure and enhancing the material's strength.
[0037] Example 3
[0038] A method for preparing a high-entropy alloy includes the following steps:
[0039] (1) Mix 8.9% Al, 18.7% Fe, 19.6% Co, 19.6% Ni, 21.2% Cu and 12% Cr metal powders by mass percentage, add zirconia grinding balls at a ball-to-material mass ratio of 10:1, load the ball powder into a vacuum ball mill jar and place it in a planetary ball mill at a speed of 300 rpm for 15 h to obtain high entropy alloy powder.
[0040] (2) Add nickel-plated carbon nanotubes to the high-entropy alloy powder obtained in step (1) and perform vacuum ball milling to mix the powder. The amount of nickel-plated carbon nanotubes added is 0.8% of the high-entropy alloy powder. The inner diameter of the nickel-plated multi-walled carbon nanotubes is 10 nm, the outer diameter is 20 nm, and the length is 30 μm. Continue vacuum ball milling for 10 h to obtain nickel-plated carbon nanotube high-entropy alloy mixed powder.
[0041] (3) The nickel-plated carbon nanotube high-entropy alloy mixed powder obtained in step (2) is directly pressed and held at a pressure of 14 MPa for 10 min without binder. Then, in a vacuum sintering furnace, the program is set with a heating rate of 10℃ / min from 0 to 200℃, holding at 200℃ for 0.5 h, and a heating rate of 5℃ / min from 200 to 1200℃, holding at 1200℃ for 2 h. The program ends and the furnace is cooled to obtain the high-entropy alloy composite material.
[0042] Depend on Figure 3 Metallographic surface analysis shows that the nickel-plated carbon nanotubes are uniformly dispersed inside the material with little agglomeration. The nickel-plated carbon nanotube additive phase with an addition amount of 0.8% has good compatibility with the matrix phase, and the voids around the additive phase are significantly reduced. At the same time, it has good hardness and good compressive strength.
[0043] Example 4
[0044] A method for preparing a high-entropy alloy composite material includes the following steps:
[0045] (1) Mix 8% Al, 16.4% Fe, 17.3% Co, 17.3% Ni, 18.8% Cu and 22.2% Cr metal powders by mass percentage, add zirconia grinding balls at a ball-to-material mass ratio of 10:1, load the ball powder into a vacuum ball mill jar and place it in a planetary ball mill at a speed of 300 rpm for 15 h to obtain high entropy alloy powder.
[0046] (2) Add nickel-plated carbon nanotubes to the high-entropy alloy powder obtained in step (1) and perform vacuum ball milling to mix the powder. The amount of nickel-plated carbon nanotubes added is 1.2% of the high-entropy alloy powder. The inner diameter of the nickel-plated multi-walled carbon nanotubes is 5 nm, the outer diameter is 10 nm, and the length is 10 μm. Continue vacuum ball milling for 10 h to obtain nickel-plated carbon nanotube high-entropy alloy mixed powder.
[0047] (3) The nickel-plated carbon nanotube high-entropy alloy mixed powder obtained in step (2) is directly pressed and held at a pressure of 14 MPa for 10 min without binder. Then, in a vacuum sintering furnace, the program is set with a heating rate of 10℃ / min from 0 to 200℃, holding at 200℃ for 0.5 h, and a heating rate of 5℃ / min from 200 to 1200℃, holding at 1200℃ for 2 h. The program ends and the furnace is cooled to obtain the high-entropy alloy composite material.
[0048] Depend on Figure 4 Metallographic surface analysis shows that nickel-plated carbon nanotubes exhibit short-range agglomeration and long-range uniformity within the material. The nickel-plated carbon nanotube additive phase with an addition amount of 1.2% has good compatibility with the matrix phase. Furthermore, with the increase of the amount of nickel-plated carbon nanotubes added, the average pore radius of the material is significantly reduced, while also exhibiting good hardness performance.
[0049] Comparative Example 1
[0050] A method for preparing a high-entropy alloy includes the following steps:
[0051] (1) Metal powders of 9.3% Al, 19.2% Fe, 20.4% Co, 20.4% Ni, 21.8% Cu and 8.9% Cr were mixed by mass percentage. Zirconia grinding balls were added at a ball-to-material mass ratio of 10:1. The balls were loaded into a vacuum ball mill jar and placed in a planetary ball mill and ball-milled at 300 rpm for 15 h to obtain high-entropy alloy powder.
[0052] (2) The high-entropy alloy powder obtained in step (1) is directly pressed and held at a pressure of 14 MPa for 10 min without binder. Then, in a vacuum sintering furnace, the program is set with a heating rate of 10℃ / min from 0 to 200℃, holding at 200℃ for 0.5 h, and a heating rate of 5℃ / min from 200 to 1200℃, holding at 1200℃ for 2 h. The program ends and the material is cooled with the furnace to obtain the high-entropy alloy material.
[0053] Comparative Example 2
[0054] A method for preparing a high-entropy alloy includes the following steps:
[0055] (1) Mix 8.9% Al, 18.7% Fe, 19.6% Co, 19.6% Ni, 21.2% Cu and 12% Cr metal powders by mass percentage, add zirconia grinding balls at a ball-to-material mass ratio of 10:1, load the ball powder into a vacuum ball mill jar and place it in a planetary ball mill at a speed of 300 rpm for 15 h to obtain high entropy alloy powder.
[0056] (2) The high-entropy alloy powder obtained in step (1) is directly pressed and held at a pressure of 14 MPa for 10 min without binder. Then, in a vacuum sintering furnace, the program is set with a heating rate of 10℃ / min from 0 to 200℃, holding at 200℃ for 0.5 h, and a heating rate of 5℃ / min from 200 to 1200℃, holding at 1200℃ for 2 h. The program ends and the material is cooled with the furnace to obtain the high-entropy alloy material.
[0057] Comparative Example 3
[0058] A method for preparing a high-entropy alloy includes the following steps:
[0059] (1) Mix metal powders of 8.4% Al, 17.8% Fe, 18.7% Co, 18.7% Ni, 20% Cu and 16.4% Cr by mass percentage, add zirconia grinding balls at a ball-to-material mass ratio of 10:1, load the ball powder into a vacuum ball mill jar and place it in a planetary ball mill at a speed of 300 rpm for 15 h to obtain high entropy alloy powder.
[0060] (2) The high-entropy alloy powder obtained in step (1) is directly pressed and held at a pressure of 14 MPa for 10 min without binder. Then, in a vacuum sintering furnace, the program is set with a heating rate of 10℃ / min from 0 to 200℃, holding at 200℃ for 0.5 h, and a heating rate of 5℃ / min from 200 to 1200℃, holding at 1200℃ for 2 h. The program ends and the material is cooled with the furnace to obtain the high-entropy alloy material.
[0061] Depend on Figure 5Metallographic surface analysis revealed that the high-entropy alloy material with equimolar ratios of elements in this system exhibited numerous micropores and partial segregation. In contrast, the composite material with added nickel-plated carbon nanotubes showed significantly more second-phase structure, indicating that the addition of carbon nanotubes can effectively alter the microstructure and achieve a more uniform composition distribution.
[0062] Comparative Example 4
[0063] A method for preparing a high-entropy alloy includes the following steps:
[0064] (1) Mix 8% Al, 16.4% Fe, 17.3% Co, 17.3% Ni, 18.8% Cu and 22.2% Cr metal powders by mass percentage, add zirconia grinding balls at a ball-to-material mass ratio of 10:1, load the ball powder into a vacuum ball mill jar and place it in a planetary ball mill at a speed of 300 rpm for 15 h to obtain high entropy alloy powder.
[0065] (2) The high-entropy alloy powder obtained in step (1) is directly pressed and held at a pressure of 14 MPa for 10 min without binder. Then, in a vacuum sintering furnace, the program is set with a heating rate of 10℃ / min from 0 to 200℃, holding at 200℃ for 0.5 h, and a heating rate of 5℃ / min from 200 to 1200℃, holding at 1200℃ for 2 h. The program ends and the material is cooled with the furnace to obtain the high-entropy alloy material.
[0066] Comparative Example 5
[0067] A method for preparing a high-entropy alloy includes the following steps:
[0068] (1) Mix 7.6% Al, 15.1% Fe, 16% Co, 16% Ni, 17.3% Cu and 28% Cr metal powders by mass percentage, add zirconia grinding balls at a ball-to-material mass ratio of 10:1, load the ball powder into a vacuum ball mill jar and place it in a planetary ball mill at a speed of 300 rpm for 15 h to obtain high entropy alloy powder.
[0069] (2) The high-entropy alloy powder obtained in step (1) is directly pressed and held at a pressure of 14 MPa for 10 min without binder. Then, in a vacuum sintering furnace, the program is set with a heating rate of 10℃ / min from 0 to 200℃, holding at 200℃ for 0.5 h, and a heating rate of 5℃ / min from 200 to 1200℃, holding at 1200℃ for 2 h. The program ends and the material is cooled with the furnace to obtain the high-entropy alloy material.
[0070] Combination Figure 7 , Figure 8It can be seen that the high-entropy alloy powder prepared under these process conditions exhibits relatively small particle size fluctuations, concentrated around 30 μm, which helps to refine the grain structure in conjunction with the sintering process, achieving the purpose of fine grain strengthening. Furthermore, when the Cr content fluctuates within a certain range, the density of the prepared high-entropy alloy reaches a high level. Especially when the Cr content is between 8.9% and 16.4%, both its density and grain refinement achieve good results, resulting in the final high-entropy alloy matrix material possessing excellent compressive strength and hardness.
[0071] Performance testing
[0072] The compressive strength and hardness properties of the high-entropy alloy composite materials obtained in Examples 1-4 and Comparative Examples 1-5 were tested, and the results are shown in Table 1.
[0073] Table 1
[0074] Example 1 422.31 209.45 Example 2 434.63. 223.34 Example 3 478.89 262.49 Example 4 434.73 206.18 Comparative Example 1 223.67 238.73 Comparative Example 2 321.21 242.34 Comparative Example 3 308.45 266.18 Comparative Example 4 294.89 156.59 Comparative Example 5 274.76 168.54
[0075] As can be seen from Table 1, adding nickel-plated carbon nanotubes can produce an alloy with good compressive strength and hardness. Furthermore, this high-entropy alloy has good corrosion resistance and can meet the service conditions of stainless steel. Therefore, it can be used as a new stainless steel material.
Claims
1. A method for preparing a high-entropy alloy composite material, characterized in that: The specific preparation steps are as follows: (1) Metal powders of 7.3%~9.3% Al, 15.2%~19.3% Fe, 16%~20.3% Co, 15.9%~20.3% Ni, 17.3%~21.9% Cu and the balance Cr are mixed and vacuum ball-milled according to the mass percentage of each metal powder, wherein the total mass percentage of each metal powder is 100%, to obtain high entropy alloy powder; (2) Add nickel-plated carbon nanotubes to the high-entropy alloy powder obtained in step (1). The amount of nickel-plated carbon nanotubes added is 0.2%~1.2% of the high-entropy alloy powder. Continue ball milling to obtain a mixed powder of nickel-plated carbon nanotubes and high-entropy alloy. (3) The nickel-plated carbon nanotube high-entropy alloy mixed powder obtained in step (2) is directly pressed into shape under a pressure of 14 MPa for 10 min. (4) The pressed powder compact is first preheated to 200℃ at a heating rate of 10℃ / min and held for 0.5h, then heated to 1200℃ at a heating rate of 5℃ / min and held for 2h, and then cooled in the furnace. The vacuum degree throughout the sintering process is less than 1*10 2 Pa, to obtain high-entropy alloy composite material; The nickel-plated carbon nanotubes have an inner diameter of 5-10 nm, an outer diameter of 10-20 nm, and a length of 10-30 μm.
2. The method for preparing the high-entropy alloy composite material as described in claim 1, characterized in that: The ball-to-material ratio in the ball milling process is 10:1, and the ball milling speed is 300 rpm; in step (1), the ball milling time is 15 hours; in step (2), the ball milling time is 10 hours.
Citation Information
Patent Citations
Carbon nano tube reinforced high-entropy alloy composite material and preparation method thereof
CN110004349A
High-powder-yield mechanical alloying and sintering forming method for high-entropy alloy
CN113528925A